2005
DOI: 10.1111/j.1600-051x.2005.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo antimicrobial effectiveness of an essential oil‐containing mouth rinse 12 h after a single use and 14 days' use

Abstract: Rinsing with the essential oil mouth rinse can have long-lasting effects in reducing anaerobic bacteria overall as well as Gram-negative anaerobes and VSC-producing bacteria. The significant reductions in numbers of these bacteria produced by the essential oil mouth rinse, both in plaque and on the dorsum of the tongue, can play a key role in explaining the essential oil mouth rinse's effectiveness in reducing supragingival plaque and gingivitis as well as its effectiveness in controlling intrinsic oral malodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 19 publications
(36 reference statements)
2
38
1
3
Order By: Relevance
“…The significant reductions in numbers of these bacteria produced by the EO mouthrinse, both in plaque and on the dorsum of the tongue, can play a key role in explaining the EO mouthrinse's effectiveness in reducing supragingival plaque and gingivitis as well as its effectiveness in controlling intrinsic oral malodor throughout the test period of 14 days. 54 …”
Section: Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant reductions in numbers of these bacteria produced by the EO mouthrinse, both in plaque and on the dorsum of the tongue, can play a key role in explaining the EO mouthrinse's effectiveness in reducing supragingival plaque and gingivitis as well as its effectiveness in controlling intrinsic oral malodor throughout the test period of 14 days. 54 …”
Section: Essential Oilsmentioning
confidence: 99%
“…10 Substrates for volatile sulfide compounds production are sulfur-containing amino-acids such as cysteine, cystine and methionine present in saliva or gingival fluid. 11 Several microorganisms recovered from periodontal lesions of gingivitis and Braz Oral Res 2008;22(Spec Iss 1): [44][45][46][47][48][49][50][51][52][53][54] periodontitis are related to produce large amounts of these volatile sulfur compounds. 10 The bacterial interactions are most likely to occur in the gingival crevices and periodontal pockets, but oral malodor can also arise from the posterior dorsal tongue.…”
Section: Halitosis and The Presence Of Oral Microorganismsmentioning
confidence: 99%
“…16 Pan et al 33 (2000) showed that bacterial phenotypes may change when the organisms go from a free floating state to a state where they are part of a biofilm. This change can result in altered susceptibilities to antimicrobial agents.…”
Section: Dental Biofilmmentioning
confidence: 99%
“…8,12 In addition, shifts in microbial profile and reductions in specific pathogens were also found. 77,78 Monitoring of other inflammatory indicators confirmed the anti-inflammatory properties of antiseptics. 11,79 Dentists were asked whether they knew if one product was superior to others.…”
Section: Effectiveness and Expected Benefits Of Mouthrinsesmentioning
confidence: 89%